KOMPETENSI KEPALA MADRASAH DALAM PELAKSANAAN DELAPAN STANDAR NASIONAL PENDIDIKAN (SNP) - ASMENDRI ASMENDRI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
The successful implementation on the Eight of Indonesia Nasional Education Standarts at madrasah is determinated by madrasah principal performance. The evaluation of madrasah principal performance need considerate to competencies of a madrasah principal. There are the five competencies of madrasah principal according to Number 13 of 2007 Permendikbud that had by madrasah principal, namely personality competency, managerial, entrepreneurship, supervision, and social. Kata kunci: Kompetensi kepala madrasah, Standar nasional pendidikan, akreditasi madrasah